2020
DOI: 10.1007/s10457-020-00516-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring transformational outcomes from donor investments in agroforestry research for development

Abstract: While many agroforestry research projects contribute to improving food security, livelihoods and management of natural resources, few have had a significant role in achieving transformational development outcomes. Evaluating the achievements and impacts of multiple research for development (R4D) projects improves understanding of how and why different development interventions work or don’t work. This paper evaluates the relative success of 15 completed agroforestry R4D projects, funded by the Australian Centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Santiago-Freijanes et al (2018) elaborated on the acceptance in European countries of agroforestry practices in arable land and pasture ecosystems in the form of hedges and isolated trees (quiet plantations) [38]. An analysis of 15 completed farm-level R4D agroforestry projects funded by the Australian Center for International Agricultural Research showed their relative success, high impact, and cumulative effect in increasing crop yields, reducing poverty, achieving sustainable management of natural resources, and generating economic benefits [39]. In Italy, silvopastoral agroforestry systems have a long history and are now widely used for food production and a variety of ecosystem services [40].…”
Section: Introductionmentioning
confidence: 99%
“…Santiago-Freijanes et al (2018) elaborated on the acceptance in European countries of agroforestry practices in arable land and pasture ecosystems in the form of hedges and isolated trees (quiet plantations) [38]. An analysis of 15 completed farm-level R4D agroforestry projects funded by the Australian Center for International Agricultural Research showed their relative success, high impact, and cumulative effect in increasing crop yields, reducing poverty, achieving sustainable management of natural resources, and generating economic benefits [39]. In Italy, silvopastoral agroforestry systems have a long history and are now widely used for food production and a variety of ecosystem services [40].…”
Section: Introductionmentioning
confidence: 99%